Characteristics of Wheat-Hemp and Wheat-Teff Models: Composite Flours - Marie Hrušková; Ivan Švec; Ivana Jurinová (Emerging Challenges in Agriculture and Food Science Vol. 5, 2022)
Model composites of wheat/hemp and wheat/teff were made as 90:10 and 80:20 w/w mixes with two distinct Czech commercial wheat flours and bright/dark forms of these non-traditional crops flour. Used analytical methods involved also insoluble, soluble and total dietary fibre contents evaluation as well as the Solvent Retention Capacity profiling. Consumer’s quality of tested composites was proven directly by baking test. Bakery products are the most important human food. In the case of hemp and teff testing, nutritious flour enrichment attained greater levels of protein (from approx. 13.0 percent approximately 30 percent vs. 6 percent) and fibre (from approx. 3.3 percent about 50 percent points vs. 30 percent points). Wheat flour SRC profiles partially differ between both standards – qualitatively better sample M was weakened by hemp flour additions, while somewhat worse sample M1 was improved by teff flour additions. The volume of bread made with bright hemp was reduced from 257ml/100 g to 196ml/100 g in baking tests, while those made with dark hemp increased to 328ml/100 g. Volumes of teff-fortified buns ranged from 325 to 369ml/100 g, compared to 381ml/100 g for regular M1. The sensory score of wheat/hemp breads was lower due to the spicy flavor and fatty aftertaste, whereas hay-like by-taste in wheat/teff bread could be tolerated with a 10% increase in the recipe.